PEMANFAATAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR SISTEM PENCERNAAN MANUSIA SEKOLAH DASAR - Diana Dwi Lestari; Ida Sulistyawati; Imas Srinana Wardani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
The purpose of this study was to describe the use of animated video media on learning outcomes of the human digestive system in elementary schools. The material about the human digestive system is certainly very difficult for elementary school students to understand because the organs involved in the digestive process cannot be observed directly. Therefore, it is necessary to use learning media that is useful for studying material related to the human digestive system properly. This research uses quantitative research, namely quasi-experimental design or quasi-exploratory method. The data sources of this study used 2 classes, namely VA with 27 students as the control class and VB class with 25 students as the experimental class. The data collection method used was a test containing 20 multiple choice questions intended to determine student learning outcomes. Based on the research results, the resulting hypothesis test proves the Asymp.Sig (2-tailed) number is 0.000 and the significance probability number is < 0.05. Therefore, the results obtained indicate that Ho is rejected. This case states that the use of animated video media affects the learning outcomes of the human digestive system in fifth grade students at SDN Keboananom Gedangan Sidoarjo.